Defiance (2008) and the Cultural Memory of Resistance in the Holocaust - William Stewart Skiles (Religions, 2025)
The film Defiance (2008) explores the true story of the Bielski Partisans in the Second World War, led by the brothers Tuvia and Zus Bielski. While the film is in many ways a conventional action-packed war story of resistance to Nazi domination during the war, the filmmakers conscientiously depicted the myriad and sundry ways Jews resisted Nazi racial hatred and the attempted extermination of European Jewry. The Bielski partisans are portrayed as violently opposing the Nazi domination and their Belorussian supporters in armed conflict; as engaging in acts of sabotage and destruction to hamper the Axis war effort; as preserving and engaging in Jewish culture and religion to ensure its propagation, even in the most extreme of circumstances; and as continually struggling for survival against Nazi efforts to murder them. Their struggle for freedom from oppression inspires these acts of resistance. Furthermore, the filmmakers explore the theological problem of understanding the Jews as God’s chosen people as they fight for their lives against Nazi policies of extermination.